KAJIAN TERHADAP INTELLECTUAL PROPERTY OFFICE OF SINGAPORE (IPOS) DALAM PENYELESAIAN SENGKETA MEREK: A Study of the Intellectual Property Office of Singapore (IPOS) in Trademark Dispute Resolution - Wahyuni, Putri Indah; Nugrahani, Aline Gratika (Faculty of Law, Universitas Trisakti, 2025)
Trademark protection will arise when the trademark is registered, this system is called the constitutive system. The use of a constitutive system provides more legal certainty than a declarative system on copyright, however, trademark registration does not terminate trademark infringements that give rise to many disputes. Trademark dispute resolution can be resolved through mediation or litigation. Based on TRIPs (Trade Related Aspect of Intellectual Property Rights), the parties can choose between the two settlements. However, dispute resolution in each TRIPs member country has differences, one of which is about time, some countries require a long dispute resolution time, some have a shorter duration. Like Singapore, through IPOS, it can resolve trademark disputes in a short time. For this reason, this paper will examine IPOS in the process of resolving trademark disputes in Singapore with a slight comparison of trademark dispute resolution in Indonesia. This study uses a normative writing method with the use of secondary data, which is supported by primary data. The nature of the research is descriptive analysis, by analyzing the data qualitatively. Based on the results, it is concluded that through IPOS, trademark dispute resolution in Singapore can be resolved through faster and cheaper administrative channels. .